كاریگه‌رى نه‌خشه‌كانى ژیرى له‌ گه‌شه‌پێدانى چه‌مكه‌ مێژووییه‌كان و ئاراسته‌ى خوێندكاران به‌ره‌و بابه‌تى مێژوو له‌ پۆلى حه‌وته‌مى بنه‌ڕه‌تى - محمد, پ.دكتۆره‌ سۆلاڤ فائق; محمد, دكتۆر بهمن صالح; رشید, لانه‌ بهزاد حمه‌ (Sulaimani Journal for Humanities, 2023)
The aim of the study is to study the effect of mental maps on the development of historical concepts and students' attitudes towards the subject of history at the seventh grade of basic schools. To achieve and verify the hypotheses, I initially make four hypotheses based on the experimental design of equal groups, which consist of two groups: the experimental group and the control group. The experimental group studied through mental maps and the control group studied the same topics through their natural condition and attempted developing historical concepts and theories and measuring the orientation by conducting tests at the beginning and the end. The study sample consisted of 32 students in the seventh grade of basic level: 16 students from the experimental group and 16 students from the control group in Mahabat Basic School for Girls at the Directorate of Eastern Education in Sulaymaniyah during the academic year 2020-2021. I searched for equality between the two groups in terms of the pupils' age, the parents' illiteracy level, the parents' profession, previous knowledge, the degree of previous years, before direction choice). Then the researcher used two criteria: The first one was a test of historical concepts, consisting of 31 multiple-choice questions: The first: the list of deliverables, fill in the blanks, true and false according to the third level of Bloom Taxonomy referring to knowledge, comprehension, and application. Then the researcher found the validity of the test which was 80% and it is considered appropriate. The second criterion is guidance which consists of 20 paragraphs, and then I started to find the validity and the exam alternative and the percentage was 80% which can be considered a good percentage. Then the researcher conducted the experiment on Thursday 02/02/2022 to Thursday 10/03/2022. Both groups were taught and three lectures were given per week. After the experiment completion and conducting tests and statistical working on the obtained data using T-Test method there were statistically significant differences of 0.05 in developing historical concepts between the average scores of the experimental group that takes intelligence maps and the disciplined group that takes the same subjects. In a normal way, and the results are in the interest of the experimental group. In light of this, the researcher prepared several suggestions and recommendations, including: Opening training courses on mental mapping strategies for teachers of social sciences in the seventh grade of basic school. Instructors of College of Basic Education should pay attention to mental maps through the course book and the teachers’ program for the subject of teaching methods. Encouraging social sciences teachers to use smart maps through their supervisors, educational and scientific supervisors who study social sciences, in a way that puts students at the center of teaching. Social sciences teachers should use mental maps in history at all levels of learning. Conducting similar studies for students of other levels in social sciences subject.